Injectable Hydrogel System for Camptothecin Initiated Nanocatalytic Tumor Therapy With High Performance - Wang, Shuntao; Zhang, Qi; Zeng, Ning; Qi, Pengyuan; Huang, Chunyu; Huang, Qinqin (Frontiers in Oncology, 2022)
Single photothermal therapy (PTT) has many limitations in tumor treatments. Multifunctional nanomaterials can cooperate with PTT to achieve profound tumor killing performance. Herein, we encapsulated chemotherapeutic drug camptothecin (CPT) and pyrite (FeS2) with dual enzyme activity (glutathione oxidase (GSH-OXD) and peroxidase (POD) activities) into an injectable hydrogel to form a CFH system, which can improve the level of intratumoral oxidative stress, and simultaneously realize FeS2-mediated PTT and nanozymes catalytic treatment. After laser irradiation, the hydrogel gradually heats up and softens under the photothermal agent FeS2. The CPT then released from CFH to tumor microenvironment (TME), thereby enhancing the H2O2 level. As a result, FeS2 can catalyze H2O2 to produce ·OH, and cooperate with high temperature to achieve high-efficiency tumor therapy. It is worth noting that FeS2 can also deplete excess glutathione (GSH) in the cellular level, further amplifying oxidative stress. Both in vivo and in vitro experiments show that our CFH exhibits good tumor-specific cytotoxicity. The CFH we developed provides new insights for tumor treatment.